Assessing the longitudinal relationship between theta‐gamma coupling and working memory performance: Neuropsychology/Neuropsychological correlates of physiologic markers of cognitive decline/Dementia. (7th December 2020) - Brooks, Heather J.; Wang, Wei; Kumar, Sanjeev; Goodman, Michelle S.; Zomorrodi, Reza; Blumberger, Daniel M.; Daskalakis, Zafiris J.; Mulsant, Benoit H.; Voineskos, Aristotle N.; Rajji, Tarek K.
Abstract: Background: Individuals with a history of depression exhibit cognitive deficits and are at high‐risk for developing dementia. In particular, they show deficits in prefrontal cortical function, e.g. executive functioning and working memory. Theta‐gamma coupling (TGC) is a neurophysiologic marker of prefrontal cortical function. In cross‐sectional studies, TGC is associated with performance on several prefrontal cortex dependent cognitive tasks. Thus, it is a promising target for interventions to enhance cognition and possibly prevent cognitive decline. However, the relationship between change in TGC and change in cognitive performance is not yet characterized. The aim of this study is to determine whether change in TGC over repeated assessments is associated with change in working memory performance at these assessments. Methods: Twenty‐seven older individuals with a history of depression (mean age = 66.18, SD = 5.43) completed the N‐back, a working memory task, at three time‐points (T0, T1 (2 weeks post T0) and T2 (90 days post T0). TGC was recorded using electroencephalography during the N‐back task. Change in TGC and N‐back performance among the three time‐points was calculated for each participant. Regression analyses were run, with change in N‐back dprime as the dependent variable, change in TGC as the independent variable, and time‐point as the fixed factor. To control for any effect of change in theta and gamma oscillations, we included also changes in theta and gamma powers as covariates. Results: We found a positive association between change in TGC and change in N‐back dprime (B = 96.5, p = 0.006), but no association between change in theta (B = 7.66e‐6, p = 0.28) or gamma (B = 1.96E‐6, p = 0.93) power. There was also no effect of time‐point (B = ‐0.32, p = 0.07), and no interaction between time‐point and TGC (B = ‐67.17, p = 0.23). Conclusion: Our results suggest enhancing TGC could enhance working memory performance irrespective of whether this enhancement happens over days or weeks. They also further support the use of TGC as a target for intervention to enhance prefrontal cortical function in individuals at high‐risk for cognitive decline, and potentially prevent decline and dementia.